Injury-related gaining momentum as external causes of deaths in Ethiopian health and demographic surveillance sites: evidence from verbal autopsy study - Kassahun Alemu Gelaye; Fasil Tessema; Befikadu Tariku; Semaw Ferede Abera; Alemseged Aregay Gebru; Nega Assefa; Desalew Zelalem; Melkamu Dedefo; Mekdes Kondal; Mesfin Kote; Mitike Molla Sisay; Wubegzier Mekonnen; et al. (Taylor & Francis Group, 2018)
Background: In Ethiopia, though all kinds of mortality due to external causes are an important component of overall mortality often not counted or documented on an individual basis. Objective: The aim of this study was to describe the patterns of mortality from external causes using verbal autopsy (VA) method at the Ethiopian HDSS Network sites. Methods: All deaths at Ethiopian HDSS sites were routinely registered and followed up with VA interviews. The VA forms comprised deaths up to 28 days, between four weeks and 14 years and 15 years and above. The cause of a death was ascertained based on an interview with next of families or other caregivers using a standardized questionnaire that draws information on signs, symptoms, medical history and circumstances preceding death after 45 days mourning period. Two physician assigned probable causes of death as underlying, immediate and contributing factors independently using information in VA forms based on the WHO ICD-10 and VA code system. Disagreed cases sent to third physician for independent review and diagnosis. The final cause of death considered when two of the three physicians assigned underlying cause of death; otherwise, labeled as undetermined. Results: In the period from 2009 to 2013, a total of 9719 deaths were registered. Of the total deaths, 623 (6.4%) were from external causes. Of these, accidental drowning and submersion, 136 (21.8%), accidental fall, 113 (18.1%) and transport-related accidents, 112 (18.0%) were the topmost three leading external causes of deaths. About 436 (70.0%) of deaths were from the age group above 15 years old. Drowning and submersion and transport-related accidents were high in age group between 5 and 14 years old. Conclusion: In this study, external causes of death are significant public health problems and require attention as one of prior health agenda.